Effect of treatment on serum glial cell line-derived neurotrophic factor in bipolar patients - Zhang, Xiaobin; Zhang, Zhijun; Sha, Weiwei; Xie, Chunming; Xi, Guangjun; Zhou, Honghui; Zhang, Yumei (Journal of affective disorders, 2010)
Post-mortem studies have demonstrated various glial deficits in different brain areas of patients diagnosed with bipolar disorder (BD). Glial cell line-derived neurotrophic factor (GDNF) is a neurotrophic factor from the transforming growth factor β family which has been implicated in the pathophysiology of BD. This study aimed to determine whether GDNF in serum was abnormal in BD, and how it responded to drug treatment of BD. Serum GDNF concentrations were measured in BD patients before treatment, after 8 weeks of drug treatment, and in control subjects using a sandwich ELISA method. Before treatment, serum GDNF was significantly lower in BD patients during both manic ( P < 0.001) and depressive ( P < 0.001) episodes than in control subjects. From baseline to remission after 8 weeks of treatment, the increase in serum GDNF was statistically significant ( P < 0.001). The present study suggests that lower GDNF levels might be involved in the pathophysiology of BD and drug treatment increases the GDNF in BD.